Do Business Cycle Conditions at the Time of Labor Market Entry Affect Future Employment Prospects? - Raaum, Oddbjørn; Røed, Knut (The Review of Economics and Statistics, 2006)
Labor market conditions at the time and place of potential entry into the labor market are shown to have a substantial and persistent effect on adult employment prospects. Individuals who face particularly depressed local labor markets when they graduate from secondary education, are—other things equal—subject to relatively high rates of nonemployment during their whole prime-age work career. Building on a unique combination of micro and macro data from Norway, we show that these effects are robust with respect to model specification and conditioning variables, and that they are not limited to individuals with a particularly disadvantaged background.